(untitled) (The Journal of Psychology and Sociology, 2012)
An important principle of palliative care is availability. Assistance should be timely, no matter wherever they may be. Creating a system of palliative care incurable patients is one of the priority areas of clinical medicine and public health in most countries. The most important thing – the desire of doctors to provide terminally ill and dying and medical care, in fact, realized with the principle of humanity of our medicine and the basic principle of human ethics.